1969
DOI: 10.1139/v69-382
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 2,3-epoxyperfluoropropionylfluoride from the mercury photosensitized oxidation of 1,3-perfluorobutadiene

Abstract: The mercury photosensitized oxidation of 1,3-C,F, gives nearly equal amounts of C F 2 0 and a new compound 2,3-epoxyperfluoropropionylfiuoride and smaller amounts of c-C3F4. The infrared (i.r.) and mass spectra of 2,3-epoxyperfiuoropropionylfluoride are presented.Canadian Journal of Chemistry, 47, 2329 (1969) We wish to report the synthesis and identifica-under all operating conditions, though their tion of 2,3-epoxyperfluoropropionylfluoride (I) absolute quantum yields varied markedly. Perfluorocyclopropen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…One is CF 2 O, and the other is the epoxy compound OCF 2 CFC­(F)O where the first O atom is bonded to both of the first two C atoms. This 2,3-epoxyperfluoro­propionyl­fluoride species has been noted before in the mercury-sensitized photolysis of O 2 /CF 2 CF–CFCF 2 mixtures . The published IR spectrum is of low resolution.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…One is CF 2 O, and the other is the epoxy compound OCF 2 CFC­(F)O where the first O atom is bonded to both of the first two C atoms. This 2,3-epoxyperfluoro­propionyl­fluoride species has been noted before in the mercury-sensitized photolysis of O 2 /CF 2 CF–CFCF 2 mixtures . The published IR spectrum is of low resolution.…”
Section: Resultssupporting
confidence: 55%
“…We can speculate about the mechanism leading to the epoxy product. Stuckey et al 35 suggested that in their mercurysensitized O 2 /C 4 F 6 system energy was transferred first to O 2 and then to C 4 F 6 , which then reacted with O 2 to yield triplet Here we note that Cl-catalyzed chemistry of the kind proposed above could accomplish the same transformation, which we illustrate in Figure 8. We can imagine two pathways from a possible ketone intermediate to the final epoxy product.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations